Cohen, T.: Thinking of others: On the talent for metaphors. Princeton University Press, 2008. 89 páginas - Bejarano, Teresa Bejarano (THÉMATA. Revista de Filosofía, 2013)
Reseña del libro de Cohen, T.: Thinking of others: On the talent for metaphors. Princeton University Press, 2008. 89 páginas